(untitled) (Journal of Biomedical Investigation, 2024)
Background: Stroke is one of the most common diseases that leads to death and varying disabilities. Mood and fatigue levels affect the depth and length of sleep of stroke survivors, leading to sleep disorders which could lead to the recurrence of stroke. Understanding the impact of sleep quality will enhance patient management. Aim: To determine the impact of depression, anxiety, and fatigue on the sleep quality of stroke survivors. Method: A cross-sectional design and consecutive sampling technique was used to recruit 50 stroke survivors. The Patient Health Questionnaire-9 was used to determine post-stroke depression, the Fatigue Severity Scale was used to determine post-stroke fatigue, the Generalized Anxiety Disorder-7 was used to determine post-stroke anxiety, and the Pittsburgh Sleep Quality Index was used to evaluate sleep quality. Spearman rank correlation coefficient was used to determine the relationship between these factors. Result: Post-stroke depression, fatigue, anxiety, and poor sleep quality were observed in 27.4%, 80.4%, 29.4%, and 23.5% of the participants, respectively. A significant relationship was observed between depression, anxiety, and sleep quality. Conclusion: Poor sleep quality may be a risk factor for depression and anxiety among stroke survivors.